The Influence of Robo Advisor, Financial Literacy, Risk Tolerance on Investment Behavior And Portfolio Performance - Luklu’un Aula; Suhita Whini Setyahuni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Research aims to explore the influence of robo-advisor usage, trust in artificial intelligence (AI), financial literacy, and risk tolerance on investment behavior and its impact on the portfolio performance of retail investors in Indonesia. This study applies a quantitative approach, collecting data from 100 respondents who use investment applications such as Bibit, Ajaib, and Bareksa through the distribution of structured questionnaires with a 5-point Likert scale. Data analysis was carried out using the Structural Equation Modeling (SEM) technique. The results indicate that the four independent variables robo-advisor usage, trust in AI, financial literacy, and risk tolerance significantly affect investment behavior, which in turn has a positive effect on portfolio performance. High trust in AI combined with strong financial literacy fosters more disciplined and rational investment behavior. These findings highlight the importance of effective AI technology integration, improving financial literacy, and managing risk preferences to enhance investment decision-making quality and financial well-being. The study contributes to behavioral finance literature and offers practical implications for fintech developers and policymakers in emerging markets.